A comparative study of cemented carbide parts produced by solvent on granules 3D-printing (SG-3DP) versus press and sinter. (June 2021) - Carreño-Morelli, E.; Alveen, P.; Moseley, S.; Rodriguez-Arbaizar, M.; Cardoso, K.
Abstract: Cemented carbide parts have been manufactured from WC-12Co granules by "Solvent on Granules 3D-Printing" and compared with reference parts produced by conventional press and sintering. SG-3DP consists in growing a green part layer-by-layer by selective solvent jetting on powder-polymer granule beds. Both 3D printed green parts and uniaxially pressed compacts have been consolidated by thermal debinding and liquid phase sintering. Further densification has been achieved by hot isostatic pressing. 3D-printed parts subjected to hot isostatic pressing exhibit 99.9% of theoretical density, 1308 ± 10 HV30 hardness and 12.1 ± 0.3 MPa∙m½ indentation toughness, which are comparable to properties of a commercial fine grained WC-12Co. Percussion drilling tests with fully dense SG-3DP drill plates have also been carried out successfully on concrete. Highlights: Solvent on granules 3D-printing" (SG-3DP) is an effective Additive Manufacturing route to produce hard metal parts. Fully dense WC-12Co parts successfully processed by SG-3DP technique followed by Hot isostatic pressing. 3D-printed part microstructure equivalent to press and sintering microstructures. 3D-printed drill bits show good shape retention and B04 porosity. Functional parts processed and successful percussion drilling tests performed.